Glioblastoma Multiforme Selective Nanomedicines for Improved Anti-Cancer Treatments - Jason Thomas Duskey; Arianna Rinaldi; Ilaria Ottonelli; Riccardo Caraffi; Chiara Alessia De Benedictis; Ann Katrin Sauer; Giovanni Tosi; Maria Angela Vandelli; Barbara Ruozi; Andreas Martin Grabrucker (MDPI AG, 2022)
Glioblastoma Multiforme (GBM) is a devastating disease with a low survival rate and few efficacious treatment options. The fast growth, late diagnostics, and off-target toxicity of currently used drugs represent major barriers that need to be overcome to provide a viable cure. Nanomedicines (NMeds) offer a way to overcome these pitfalls by protecting and loading drugs, increasing blood half-life, and being targetable with specific ligands on their surface. In this study, the FDA-approved polymer poly (lactic-co-glycolic) acid was used to optimise NMeds that were surface modified with a series of potential GBM-specific ligands. The NMeds were fully characterised for their physical and chemical properties, and then in vitro testing was performed to evaluate cell uptake and GBM cell specificity. While all targeted NMeds showed improved uptake, only those decorated with the-cell surface vimentin antibody M08 showed specificity for GBM over healthy cells. Finally, the most promising targeted NMed candidate was loaded with the well-known chemotherapeutic, paclitaxel, to confirm targeting and therapeutic effects in C6 GBM cells. These results demonstrate the importance of using well-optimised NMeds targeted with novel ligands to advance delivery and pharmaceutical effects against diseased cells while minimising the risk for nearby healthy cells.